I want to solve this equation
-0.5+ 0.5*a*exp(-x-b*c) -(x-d)/e=0
where a,b,c,d are known quantities that change in each iteration of the algorithm.
So, I use the following code
Myfun = @(x, a, b, c,d,e) -0.5+ 0.5*a*exp(-x-b*c) -(x-d)/e;
A=fzero(@(x)Myfun(x, a, b, c,d,e),x0);
However, I noticed that this code is slow. So I tried something like
while abs(ff) > 0.0001
ff= -0.5+ 0.5*a*exp(-x-b*c) -(x-d)/e;
g=-0.5*a*exp(-x-b*c) -1/e ;
x = x - ff/g;
where g is the first derivative of the main function ff.
But I do not get similar solutions. Do you thing that the second piece of code is wrong?